Using social networks for Competitive Intelligence - Feige, Tomáš (2012)
This thesis focuses on the area of competitive intelligence with the emphasis on new possibilities and opportunities in relation to modern social networks. First it gives general analysis of the current state of competitive intelligence market as a whole and then deals with individual major leaders and their products, thus providing detailed overview of this business segment. It also discusses the possibilities of using social networks and other social or soft sources for competitive intelligence. Practical part of the thesis then demonstrates the theoretical knowledge on a real life CI project, which took place in early 2012 in cooperation with experts from IBM, including some interesting results and findings in appendix. The whole chapter can be used as a reference model for future projects with similar goals.